Simultaneous acute appendicitis with right testicular torsion - Tanveer Akhtar; Pranjal Kumar Das; Nitin Singh; Haralappa Paramesh (Wolters Kluwer Medknow Publications, 2012)
We present a child with both acute appendicitis and torsion of the right testis presenting at the same time. Testicular torsion possibly occurring due to vomiting in acute appendicitis so far has not been reported in the literature.